The influence of financial awareness and the utilization of artificial intelligence on financial decision making of students at the State Islamic University of North Sumatra - M. Fikri Tanjung; Atika Atika; Marliyah Marliyah (Indonesia Auditing Research Journal, 2026)
This study uses a quantitative method with a causal associative relationship to analyze the influence of financial awareness and the role of AI on the structure of financial decision-making among UINSU students. Primary data collection comes from a 5-level Likert-scale questionnaire distributed to a sample of 100 students. To ensure the accuracy of the multiple linear regression output, SPSS software is used to execute the analysis stages including: instrument reliability and validity testing, fulfillment of classical assumptions (consisting of normality, freedom from heteroscedasticity, and absence of multicollinearity), and significance evaluation (t-test, F-test, plus the achievement of the coefficient of determination). The output of this research shows a tendency for a positive and significant relationship between variables. Independently, the growth of financial awareness and the appropriate application of AI can stimulate students' financial decisions to become more mature. This conclusion is strengthened by simultaneous testing which shows that the combination of these two factors plays an essential role in influencing the financial behavior of students at the State Islamic University of North Sumatra.